The Value of Formative Action within the Networks of Globalized Biocapitalism - Costa, Massimiliano (Formazione & insegnamento, 2014)
Bio-capitalism expresses an athropho-genetic model, i.e. of “the production of man through man”, which produces economical value by extracting it not only from the operating body as material instrument of work, but also from the body taken as a whole on its rationality, creativity and emotionality. In this paper this model is challenged by the recognition of human agency not merely taken as rational and productive conformity of technique, but as ability to activate acts having their dynamic end on their own. To call for the value of human agency in bio-capitalism urges the search for the formative as set of directionality, selectivity and systematic human interaction characterising the human being as plural and open condition, both process and problem. The research should therefore investigate thegenerativity of human agency in biocapitalisc networks as conscious and active freedom within which the practices and experiences of globalized multi membership can create man value from his being with the world. Pedagogy in this context has to be tied to the man-as-freedom, and be thought beyond biotechnological rationality, in a conscious, responsible and free multi directional training played on interpretation and inter subjective interaction (on the self, on the self in the world, on the world, etc.. ).